Smoking Behavior in Makassar State Middle School Students, South Sulawesi Province - Hilal, Achmad; Zulham, Zulham; Susanto, Susanto; Nurhayati, Nurhayati; Nashrulloh, Dewi; Sari, Lely Meriaya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Cigarettes are an industrial product and international commodity that contain around 300 chemical ingredients. The purpose of this research is to determine smoking behavior among students at Makassar State Middle School. The type of research used is quantitative with a descriptive approach using total sampling technique. Data was collected by distributing questionnaires to respondents to see frequency distribution. The results of the study showed that the level of knowledge of respondents about the dangers of smoking was in the good category, namely 57 people (71.2%), while people's attitudes about the dangers of smoking were in the positive category, namely 16 people (20.0%), for the influence of society in handling the dangers. smoking in the good category, namely 57 heads of families (71.2%). From the results of this study, it was concluded that the knowledge, attitudes of students and community influences regarding the dangers of smoking were quite good. To increase students' knowledge, it is necessary to conduct counseling and seminars about the dangers of smoking to help increase students' knowledge.